Efectos de tres sustratos orgánicos en la crianza de Eisenia foetida, lombriz roja en el distrito de Yurimaguas – Loreto, 2022 - Padilla del Aguila, Jens Axel (2024)
The research was carried out at the Yurimaguas Km 17 Research and Teaching Center, of the National University of the Peruvian Amazon - UNAP. The objective was to evaluate the effect of three organic substrates on the breeding of Eisenia foetida, Red Worm in the district of Yurimaguas – Loreto. The data were analyzed through a Completely Block Design with 4 treatments and 4 repetitions. The treatments were: T1: 100% black earth; T2: 40% black soil + 60% cattle manure; T3: 30% black earth + 50% cow dung + 20% kudzu leaves and T4: 20% black earth + 40% cow manure + 20% kudzu leaves + 20% organic fruit waste. The experimental phase lasted 4 months. The best results were achieved in T2: Humus production (417.40 kg); Population increase (23,442 worms); and biomass weight of the worm (11,376 kg); In relation to the best length of the worm, it was obtained in T3 with 6.65 cm. Significant statistical differences were found when evaluating the variables. Concluding in general terms that, with the application of the organic substrate based on black earth and cow manure, it influenced the production and nutritional quality of the humus from the rearing of Eisenia foetida, a red worm in the district of Yurimaguas - Loreto.